Peranan kepolisian dalam penanggulangan pelanggaran lalu lintas oleh anak ditinjau dari perspektif pemidanaan di indonesia - Husni Yazid (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Currently, the number of motorcycles in Indonesia is experiencing a significant increase. The number of children riding motorcycles is increasing, especially school children. They believe that riding a motorcycle to school is more efficient, faster, and more economical. However, many of their riding equipment does not comply with applicable standards due to a desire to stand out from others. Child drivers are known for their unsafe and disorderly driving behavior. Such as driving with more than two people without wearing helmets, uncontrolled speed, driving without a driver's license, sing racing exhausts, and running red lights. This study uses a normative juridical approach. Data collection was carried out through literature studies in orderto obtain secondary data, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of the study, it is known that the role of the police in dealing with child traffic violations is vital to ensuring safety on the highway. By using a preventive and firm approach, the police not only enforce the law but also shape more responsible driving behavior among children.Diversion and restorative justice are part of the police's efforts to create solutions thatinvolve the guidance and education of children. Collaboration with families, schools,and related institutions is key to creating an environment that supports the development of children as safe road users. Along the way, the police also play a role in fostering a positive traffic culture. Despite measures such as counseling, law enforcement, and restorative justice, challenges remain in reducing the rate of child traffic violations. Better coordination is needed between the police, schools, parents, and the community as a whole to create a more conducive, safe, and positive environment for both children and the community at large